2020
DOI: 10.1186/s12909-020-01995-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between academic self-efficacy, learning-related emotions, and metacognitive learning strategies with academic performance in medical students: a structural equation model

Abstract: Recognition of the factors affecting the medical students' academic success is one of the most important challenges and concerns in medical schools. Hence, this study aimed to investigate the mediating effects of metacognitive learning strategies and learning-related emotions in the relationship between academic self-efficacy with academic performance in medical students. Methods: The present study was carried out on 279 students of medicine studying at Shiraz University of Medical Sciences. The students fille… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
179
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(291 citation statements)
references
References 50 publications
16
179
2
13
Order By: Relevance
“…We found that mastery approach-oriented students, whose priority is the development of competencies and skills, deeper learning and personal satisfaction, presented higher scores on one of the MAI domains (knowledge about cognition, p = 0.003, median 0.71, IQR 0.23). These findings corroborate the findings in the available literature about metacognition by reinforcing its relationship with better learning strategies, academic performance and academic success [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that mastery approach-oriented students, whose priority is the development of competencies and skills, deeper learning and personal satisfaction, presented higher scores on one of the MAI domains (knowledge about cognition, p = 0.003, median 0.71, IQR 0.23). These findings corroborate the findings in the available literature about metacognition by reinforcing its relationship with better learning strategies, academic performance and academic success [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…It was demonstrated that higher levels of SRL are associated with higher academic achievement, more success in learning clinical skills and better mental health outcomes [ 8 ]. However, few studies have focused on the relationship among the components of SRL in medical students [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, and within the relational context, the emotions that arise in university students could predict their academic coping strategies, their willingness to learn [7] and their best performance [8]. In particular, the emotional intelligence of students becomes especially important as they are exposed to challenging interpersonal situations in contexts unknown to them [9].…”
Section: Introductionmentioning
confidence: 99%